Enzymatic inhibition of MICA sheddase ADAM17 by lomofungin in hepatocellular carcinoma cells. Issue 10 (22nd September 2018) - Arai, Jun; Goto, Kaku; Tanoue, Yasushi; Ito, Sayaka; Muroyama, Ryosuke; Matsubara, Yasuo; Nakagawa, Ryo; Kaise, Yoshimi; Lim, Lay Ahyoung; Yoshida, Hitoshi; Kato, Naoya
Abstract : In our previous study on hepatocellular carcinoma (HCC) susceptibility genes in chronic hepatitis patients, we identified the MHC class I polypeptide‐related sequence A (MICA). Natural killer cells eliminate various cancer cells, including HCC, by suppressing MICA shedding. Therefore, we investigated MICA sheddases and inhibitors for HCC immunotherapy. In this study, HepG2, PLC/PRF/5, and Hep3B were treated with the siRNA of a disintegrin and metalloproteases (ADAMs) and matrix metalloproteases to measure the concentration of soluble MICA (sMICA) by ELISA to detect the therapeutic target. Furthermore, an FDA‐approved drug library was tested for the enzymatic inhibition of the targeted enzyme in an in vitro drug screening assay system. ADAM17 knockdown reduced sMICA levels and increased membrane‐bound MICA (mMICA) expression in HCC cells. In an in vitro drug screen using an FDA‐approved drug library, lomofungin, an antifungal drug, was found to strongly decrease ADAM17 activity. In HCC cells, mMICA expression was induced and sMICA production was inhibited in a dose‐dependent manner. These effects were cancelled upon ADAM17 knockdown, suggesting that lomofungin targeted ADAM17. Analysis of lomofungin analogs revealed the responsible functional groups. In summary, we suggest lomofungin to be an attractive agent for the immunological control of HCC, via the suppression of ADAM17. Abstract : What's new? Targeting immune escape mechanisms of cancer cells is an attractive therapeutic approach. Here the authors follow up on a previous observation identifying membrane‐bound major histocompatibility complex class I‐related chain A (MICA) as a natural killer cell ligand on cancer cells. They show that ADAM17, a disintegrin and metalloprotease, sheds MICA as a decoy in hepatocellular carcinoma as soluble MICA levels increase after knockdown of ADAM17 or treatment with lomofungin, an antifungal drug newly found to inhibit ADAM17 activity. These data establish lomofungin as a new drug candidate for immunotherapy in liver cancer.